Biopigments from Monascus: strains selection, citrinin production and color stability - Júlio Cesar de Carvalho; Bruno Oliva Oishi; Ashok Pandey; Carlos Ricardo Soccol (Brazilian Archives of Biology and Technology, 2005)
Fungi form the genus Monascus are a promising source for natural color additives. However, before effectively applying Monascus to foods, it is important to select strains which produce large amounts of biopigments but little or no citrinin, a mycotoxin usually also produced by these fungi. Also, color stability of these pigments should be properly investigated. In order to compare Monascus strains for biopigment production in solid substrate fermentation (SSF), 4 strains (NRRL 1991, NRRL 2897, CCT 3802 and LPB 31) were cultivated over PDA in Petri dishes, and compared for radial growth velocity. Also, these strains were cultivated over cooked rice, and compared in relation to their capacity to produce biopigments and citrinin. The results showed that the strain LPB 31 is the best strain for biopigment production in SSF, giving both higher pigment concentration and lower citrinin concentration on the extracts, showing that it is a promising strain for production of this bioproduct. Biopigmentassays for heat and pH stability, show that these biopigments are unstable at low pH and high temperatures, but may be successfully used at near-neutrality pH's and in non-thermal processed foods. Fungos do gênero Monascus são uma fonte promissora de corantes vermelhos naturais. No entanto, antes de se aplicar Monascus a alimentos, é importante selecionar linhagens capazes de produzir grandes quantidades de pigmentos, com o mínimo possível de citrinina. Além disso, a estabilidade de cor desses pigmentos deve ser adequadamente investigada. Com o objetivo de comparar linhagens de Monascus para a produção de biopigmentos em fermentação em substrato sólido (FSS), 4 linhagens (NRRL 1991, NRRL 2897, CCT 3802 e LPB 31) foram cultivadas sobre PDA em placas de Petri, e comparadas com relação à velocidade de crescimento radial. Além disso, essas linhagens foram cultivadas em arroz cozido, e comparadas quanto à sua capacidade de produção de biopigmentos e de citrinina. Os resultados mostram que a linhagem LPB 31 é a melhor linhagem para produção de biopigmentos em FSS, dando tanto maior concentração de pigmentos quanto menor concentração de citrinina, mostrando que se trata de uma linhagem promissora para a obtenção deste bioproduto. Os biopigmentos extraídos dos substratos fermentados foram testados quanto à estabilidade frente ao calor e ao pH, mostrando que os biopigmentos de Monascus são instáveis em pH's baixos e altas temperaturas, mas que podem ser usados sem problema em condições de neutralidade, em alimentos sem processamento térmico.